Integrated transcriptome and single-cell sequencing analysis identify blood-pancreas shared lncRNA biomarkers in new-onset T2DM - Yan Wang; Yangming Qu; Mingxin Dong; Yulong Zhang; Na Zhao; Suli Song; Mingyang Huo; Nan Lu; Baichuan Chen; Chengbiao Sun; Kaikai Yu; Juan Ren; et al. (PLoS ONE, 2026)
Type 2 diabetes mellitus (T2DM) is characterized by β-cell dysfunction and insulin resistance, yet the early molecular drivers remain elusive. This study set out with the aim of identifying blood-pancreas shared long non-coding RNAs (lncRNAs) as potential systemic biomarkers in treatment-naïve patients with new-onset T2DM. We integrated transcriptome sequencing of peripheral blood from 8 T2DM patients and 8 controls with single-cell RNA sequencing (scRNA-seq) of pancreatic islets from an independent cohort. Differential expression analysis revealed 1,709 dysregulated lncRNAs in peripheral blood, of which 257 were identified as high-priority candidate through weighted gene co-expression network analysis (WGCNA). Further intersection with scRNA-seq data from 17 T2DM donors identified 157 β-cell-specific mRNAs co-expressed with 135 blood-derived lncRNAs. Functional enrichment analysis implicated these genes in chromatin remodeling, focal adhesion, and neurodegenerative pathways. Validation in an expanded cohort (85 T2DM vs. 85 controls) confirmed significant downregulation of ENST00000473095, MSTRG.90147.1 and ENST00000531992 in T2DM. The combined ROC-AUC value of these three lncRNAs was 0.73, which exceeds the AUCs of each individual lncRNA (0.61–0.64). Our findings tentatively suggest that blood-derived lncRNAs as early biomarkers reflecting β-cell stress and systemic dysregulation. These lncRNAs may potentially bridge peripheral blood biomarkers with tissue-specific pathophysiology in T2DM.